2005
DOI: 10.1002/mop.21355
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐wideband rectangular dielectric resonator antenna for WLAN communications

Abstract: ABSTRACT:A dual and wideband single-element rectangular dielectric resonator antenna (DRA) excited by a microstrip aperture is investigated experimentally. It provides two passbands in the ranges of 2. which INTRODUCTIONThe dielectric resonator antenna (DRA) has been of great interest in the last two decades because of its various advantages, such as small size, light weight, low loss, low cost, and ease of excitation [1,2]. Although the relatively high bandwidth of the DRA is sufficient for many practical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…FEKO simulated radiation patterns of the prototype antenna whose dimensions are shown in Table I. 5.875 GHz (right) over a path that includes the top and bottom strips of the monopole and the resonator arms.…”
Section: Current Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…FEKO simulated radiation patterns of the prototype antenna whose dimensions are shown in Table I. 5.875 GHz (right) over a path that includes the top and bottom strips of the monopole and the resonator arms.…”
Section: Current Distributionsmentioning
confidence: 99%
“…Designs range from those based on monopoles with stub-tuning [1], [2], sleeve dipoles [3], or multibranch [4] to those based on dielectric resonators [5]. Recently, it has been demonstrated that loading with "metamaterial particles" can also facilitate dual-band operation [6].…”
Section: Introductionmentioning
confidence: 99%
“…A dual-band antenna is a key component for such communication systems [3][4][5][6][7][8][9], especially for "universal" applications, where it should be covering the whole 2.4-2.484 GHz and 5.15-5.825 GHz bands for dual-band WLAN. Designs range from those based on branched monopole [3,4], dipole [5,6], or multibranch [7,8] to those based on dielectric resonators. Recently, it has been demonstrated that loading with magnetic resonator can facilitate dual-band operation [9].…”
Section: Introductionmentioning
confidence: 99%
“…For implementations, configurations such as printed dipole [1], F-shaped monopole [3], stack inverted-F monopole [2,4], double-T monopole [5,6], rectangular slot [7], reconfigurable geometry [8], double S-shaped monopole [9], triangular slot [10], Gshaped monopole [11], C-shaped monopole [12], double ring slot [13], hock-shaped monopole [14], rectangular dielectric resonator [15], and shorted parasitic patches [16], etc. have been developed.…”
Section: Introductionmentioning
confidence: 99%